Signaling Fiscal Regime Sustainability - Prati, Alessandro; Drudi, Francesco (Washington, D.C. : International Monetary Fund, 1999)
This paper proposes a signaling model that offers a new perspective on why governments deviate from optimal tax smoothing and delay debt stabilization. In our model, dependable-but not fully credible-governments have an incentive to tighten the fiscal regime when the signaling effect on credit ratings is larger (that is, when a sufficiently large stock of debt has been accumulated). At this point, they may deviate from tax smoothing not to be mimicked by weak governments. The model predicts that primary balances and debt stocks are complementary inputs in the credit rating function as tests on Italian, Irish, Belgian, and Danish data show.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet